2017
DOI: 10.1017/cjn.2017.271
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Abnormal CSF Neurotransmitter Metabolite Profiles in a Pediatric Tertiary Care Centre

Abstract: Acknowledging the limitations of this retrospective chart review, we conclude that, in our cohort, in addition to patients with movement disorders, a considerable number of patients with epilepsy and epileptic encephalopathy also showed secondary neurotransmitter mono-amine abnormalities. There is no clear relation, however, between clinical phenotype and type of neurotransmitter affected. In addition, no association was identified between the type of antiseizure medications and affected neurotransmitter type.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies showed abnormalities for both serotonin and dopamine metabolites at a rate of about 20%. 6,7,18 The higher prevalence of abnormalities in our series could be related to the fact that our study only included patients with epilepsy onset below 3 years of age, while previous studies include older ages at onset and other conditions such as movement disorders and neurodevelopmental delay with or without epilepsy.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed abnormalities for both serotonin and dopamine metabolites at a rate of about 20%. 6,7,18 The higher prevalence of abnormalities in our series could be related to the fact that our study only included patients with epilepsy onset below 3 years of age, while previous studies include older ages at onset and other conditions such as movement disorders and neurodevelopmental delay with or without epilepsy.…”
Section: Discussionmentioning
confidence: 96%
“…To make the concept applicable in clinical practice, development of criteria similar to those available for diagnosing metabolic syndrome might be beneficial, but instead exclusively with focus on biochemical compounds (eg, specific neurotransmitter abnormalities, such as high levels of CGRP). Development of such criteria could also be guided by construction of networks and subsequent identification of hub proteins (eg, within each subgroup) .…”
Section: Thoughts Regarding Utility and Future Studiesmentioning
confidence: 99%